Images, improvisations, sound, and silence from 1000 to 1800 : degree zero - Hellemans, Babette; Hellemans, Babette; Nelson, Alissa Jones; Nelson, Alissa Jones (Knowledge communities, 2018)
Cover; Table of Contents; Preface and Acknowledgements; Ouverture; Images; 1 The Two Bodies of the Virgin; 2 The Three Ages of Man and the Materialization of an Allegory; 3 Lapsus figurae; Improvisations; 4 Drawing a Line and Questioning Art; 5 Fall and Rise Again; 6 Improvisation as a Chief Pillar of the Poetic Art in Persian Literary Tradition; Sound; 7 Intending the Listener; 8 The Sovereign Ear; 9 Where Sound and Meaning Part; Silence; 10 Writing about Silence and the Secret in the Twelfth Century; 11 An Arrangement of Silence; 12 Dimidia Hora; List of Contributors; Index